2012
DOI: 10.1038/sc.2011.160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an exercise programme on musculoskeletal and neuropathic pain after spinal cord injury—results from a seated double-poling ergometer study

Abstract: Objectives: To assess pain relieving effects of an intensive exercise programme on a seated double-poling ergometer in individuals with spinal cord injury (SCI). Setting: Stockholm, Sweden. Methods: A total of 13 wheelchair-dependent individuals with a thoracic or lumbar SCI were recruited to a 10-week training period (three times weekly) assessing the effects of regular training on upper-body strength, aerobic and mechanical power, and crossover effects on functional performance, as well as cardiovascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 21 publications
0
57
1
1
Order By: Relevance
“…With regard to the effects of exercise on pain after SCI, Norrbrink et al (12) used a seated double-poling ergometer for 10 weeks and reported that NP intensity after SCI was decreased by aerobic exercise. In addition, Kressler et al (10) showed that pain after SCI was decreased by overground bionic ambulation training for 6 weeks, and Cruciger et al (11) observed that gait training with a robot suit decreased pain after SCI in 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the effects of exercise on pain after SCI, Norrbrink et al (12) used a seated double-poling ergometer for 10 weeks and reported that NP intensity after SCI was decreased by aerobic exercise. In addition, Kressler et al (10) showed that pain after SCI was decreased by overground bionic ambulation training for 6 weeks, and Cruciger et al (11) observed that gait training with a robot suit decreased pain after SCI in 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported recently that gait or aerobic exercises improve NP, such as that after SCI (10)(11)(12). Moreover, this has led to a renewal of interest in exercises that can decrease pain after SCI.…”
mentioning
confidence: 99%
“…[14,15] Being physically active has been shown to reduce levels of perceived musculoskeletal and neuropathic pain, decrease the risk factors of cardiovascular disease and type 2 diabetes, and lead to greater functional capacity such as ease of transfer thereby improving SWB. [16][17][18] Moreover, PA can impact SWB through reducing depression, enhancing physical self-concept and increasing life satisfaction, [19,20] and improve PWB through facilitating experiences (such as personal control, responsibility and risk taking) that promote post-traumatic growth. [21] Yet despite the array of health and well-being benefits to be gained from regular PA, most people with SCI live insufficiently active lifestyles with an estimated 50% completely sedentary.…”
Section: Introductionmentioning
confidence: 99%
“…Various neuro-rehabilitative approaches are utilized to promote plasticity and assist recovery. 77 Future work should address the influence of time since injury on the impact of exercise in spinal cord injury, as compensatory measures will likely develop over a period of months to years. This is followed by active exercises to promote plasticity both caudal and rostral to the lesion level.…”
Section: Spinal Cord Injurymentioning
confidence: 99%